2012
DOI: 10.1002/etc.1716
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal absorption, metabolic debromination, and hydroxylation of three commercial polybrominated diphenyl ether mixtures by common carp

Abstract: Abstract-The gastrointestinal absorption, metabolic debromination, and hydroxylation of three commercial brominated diphenyl ether (BDE) mixtures were separately studied in juvenile common carp. The absorption rate of penta-BDE was higher than that of octa-and deca-BDE, likely because of the lower molecular volumes of its major congeners. However, no significantly positive relationships were found between the number of bromine atoms and the absorption rate, especially for congeners with a bromine atom number l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
36
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 37 publications
(64 reference statements)
12
36
1
1
Order By: Relevance
“…This finding suggests that the increased abundance of BDE-47 in fish was a result of the debromination of BDE-99. As for BDE-100, its relative contribution to the total PBDE in Penta-BDE was similar to its contribution in the fish carcasses (8.2% vs. 8.4%) (Zeng et al, 2012), indicating a constant δ 13 C value before and after the exposure experiments. In brief, this study verified the applicability of CSIA for determining the fate of PBDEs in biota.…”
Section: Application To Laboratory-exposed Common Carpmentioning
confidence: 64%
See 4 more Smart Citations
“…This finding suggests that the increased abundance of BDE-47 in fish was a result of the debromination of BDE-99. As for BDE-100, its relative contribution to the total PBDE in Penta-BDE was similar to its contribution in the fish carcasses (8.2% vs. 8.4%) (Zeng et al, 2012), indicating a constant δ 13 C value before and after the exposure experiments. In brief, this study verified the applicability of CSIA for determining the fate of PBDEs in biota.…”
Section: Application To Laboratory-exposed Common Carpmentioning
confidence: 64%
“…The abundance of BDE-47 compared to total PBDEs increased from 30% in the Penta-BDE mixture to 85% in fish, whereas the contribution of BDE-99 to total PBDE decreased from 47% in the Penta-BDE mixture to 0.47% in fish (Zeng et al, 2012). A previous study conducted by Stapleton et al (2004) demonstrated that common carp can transform BDE-99 to BDE-47.…”
Section: Application To Laboratory-exposed Common Carpmentioning
confidence: 77%
See 3 more Smart Citations